Programmable Matter: The Nanoparticle Atom and DNA Bond. Issue 12 (6th February 2022) - Samanta, Devleena; Zhou, Wenjie; Ebrahimi, Sasha B.; Petrosko, Sarah Hurst; Mirkin, Chad A.
Abstract: Colloidal crystal engineering with DNA has led to significant advances in bottom‐up materials synthesis and a new way of thinking about fundamental concepts in chemistry. Here, programmable atom equivalents (PAEs), comprised of nanoparticles (the "atoms") functionalized with DNA (the "bonding elements"), are assembled through DNA hybridization into crystalline lattices. Unlike atomic systems, the "atom" (e.g., the nanoparticle shape, size, and composition) and the "bond" (e.g., the DNA length and sequence) can be tuned independently, yielding designer materials with unique catalytic, optical, and biological properties. In this review, nearly three decades of work that have contributed to the evolution of this class of programmable matter is chronicled, starting from the earliest examples based on gold‐core PAEs, and then delineating how advances in synthetic capabilities, DNA design, and fundamental understanding of PAE‐PAE interactions have led to new classes of functional materials that, in several cases, have no natural equivalent. Abstract : Programmable atom equivalents (PAEs) are nanoparticles functionalized with a dense shell of DNA containing short single‐stranded regions called "sticky ends." When PAEs with complementary sticky ends interact, hybridization leads to DNA "bonds" between nanoparticles. PAEs can be assembled into crystalline arrangements where unlike atomic systems, the "atom" (nanoparticle) and "bond" (DNA) can be tuned independently to yield designer materials.